The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10165719
|View full text |Cite
|
Sign up to set email alerts
|

The Optomechanical Response of a Cubic Anharmonic Oscillator

Abstract: The nonlinearity of a mechanical oscillator may lead to the generation of the macroscopic quantum states, which are useful for precision measurement. Measuring the nonlinearity of a mechanical oscillator becomes important in order to effectively assess its performance. In this paper, we study the electromagnetically induced transparency (EIT) in an optomechanical system with a cubic nonlinear movable mirror. In the presence of the nonlinearity of the movable mirror, we show that the intensity of the output pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Here we assume the cubic mechanical nonlinearity strength is real and positive (α > 0). It has been estimated that the cubic mechanical nonlinearity strength α can be about 1.2 × 10 8 N/m 2 [32] by coupling a linear movable mirror to a three-level system [28].…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we assume the cubic mechanical nonlinearity strength is real and positive (α > 0). It has been estimated that the cubic mechanical nonlinearity strength α can be about 1.2 × 10 8 N/m 2 [32] by coupling a linear movable mirror to a three-level system [28].…”
Section: Modelmentioning
confidence: 99%
“…During the last decade, it has been reported that the large mechanical nonlinearity can be engineered by coupling a linear mechanical resonator to a low-dimesional additional system [28], enhancing the intrinsic geometric nonlinearity of the mechanical resonator with the help of electrostatic fields [29], and using the thermal energy of the levitated nanomechanical oscillator [30]. Moreover, it has been shown that the mechanical nonlinearity in a cavity optomechanical system can be measured from the phase change of a cavity field using a four-pulse interaction [31] and the transparency peak shift of a weak coherent probe field [32]. In addition, the mechanical nonlinearity in an optomechanical system can be used to achieve the self-oscillation [33], enhance the second-order generation [32], entangle the two nanomechanical qubits [34], prepare a single-phonon Fock state [35] and the mechanical squeezed state [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its important research value in quantum communication and quantum computing [2] and ultrasensitive force measurement [3], cavity optomechanics has received considerable attention. Recent experiments have proved the possibility of cooling the mechanical oscillator to the quantum ground state in a cavity optomechanical system [4,5], which enables us to explore many nonlinear optical phenomena in optomechanical systems [6][7][8], such as the non-classical correlations between phonons and single photons [9], entanglement between mechanical and optical resonators [10,11], parametric normal-mode splitting [12][13][14], and mechanical compression state below zero point fluctuation [15][16][17]. In addition, electromagnetic induced transparency (EIT) effect has been widely discussed in quantum optics.…”
Section: Introductionmentioning
confidence: 99%
“…In the frame of this model in optomechanics, the possibility of precision measuring electrical charge with optomechanically induced transparency [31], Coulomb-interaction-dependent effect of high-order sideband generation [32] as well as force-induced transparency and conversion between slow and fast lights [33] have been studied. Recently, the elec-tromagnetically induced transparency with a cubic nonlinear movable mirror has been considered [34]. Steadystate mechanical squeezing via Duffing and cubic nonlinearities was analyzed [35].…”
Section: Introductionmentioning
confidence: 99%